Behavior Science and Environmental Health Policy: Methylmercury as an Exemplar. (March 2017) - Newland, M. Christopher; Bailey, Jordan M.
Environmental levels of hazardous chemicals, including methylmercury (MeHg), are manyfold higher now than during the preindustrial era. Behavior analysis and other basic and clinical sciences have contributed significantly to identifying and characterizing the neurobehavioral effects of these chemicals, often well before knowing the biological mechanisms of toxicity. The study of MeHg illustrates how our contemporary understanding of the motor, sensory, and cognitive effects of exposure has come from experimental laboratory models using advanced behavioral techniques, as well as carefully planned studies of exposed populations. These have informed environmental policies related to MeHg's release into the environment and human consumption of this contaminant. Toxicity assessments based on only existing approaches to human cognitive testing, however, might underestimate its adverse effects because they do not reflect the complete picture of MeHg's behavioral toxicity. Basic and applied behavioral science should have a future role in environmental policy decisions.